On a functional equation for Dido’s problem - Kahlig, Peter; Matkowski, Janusz (Annales Mathematicae Silesianae, 1999)
By some geometrical considerations we formulate a functional equation which is related to the ancient isoperimetric problem of Dido. The continuous solution of this Dido functional equation depends on an arbitrary function. However, we show that in a class of functions of suitable asymptotic behavior at infinity, the Dido functional equation has a one-parameter family of "principal" solutions. Some applications are given.